The broken road [compact disc, unabridged] - Evans, Richard Paul (Simon & Schuster Audio, 2017)
A hotshot New York businessman thought he'd achieved the American dream, even though his success depended on get-rich-quick schemes that drained the bank accounts of hopeful entrepreneurs. But when his five-star life begins ripping at the seams, he begins to doubt the world he's built for himself. Disgusted by his lifestyle, his wife leaves him and moves to California, and soon after he learns that one of his financially ruined customers committed suicide. When a plane the businessman was supposed to be on crashes, killing all of its passengers, he feels he's been given a second chance. So he begins his journey across Route 66 in search of meaning, reflection, and, ultimately, redemption.